Now you're playing with audience power: the work of watching games. Issue 4 (7th August 2016) - Taylor, Nicholas Thiel
ABSTRACT: As electronic sports (e-sports)—the configuration of competitive videogaming as spectator sport—surges in popularity, industry organizations such as Major League Gaming (MLG) continue to experiment with techniques for capturing, and capitalizing on, the work of watching play. This article critically considers these techniques of "audiencing" by comparing observations of two MLG tournaments, in 2008 and 2012, situating them within broader cultural, technological, and economic transformations in the competitive gaming landscape. Even as games continue to be lauded as "participatory" media, this account shows a shift within some e-sports contexts towards rebuilding, rather than blurring, the boundaries between content producers and audiences.